2020
DOI: 10.1093/ehjci/ehaa946.1592
|View full text |Cite
|
Sign up to set email alerts
|

The gut hormone GLP-2 predicts cardiovascular risk in patients with acute myocardial infarction

Abstract: Background GLP-1 and GLP-2 (glucagon-like peptide-1/2) are gut derived hormones that are co-secreted from intestinal L-cells in response to food intake. While GLP-1 is known to induce postprandial insulin secretion, GLP-2 enhances intestinal nutrient absorption and is clinically used for the treatment of patients with short bowel syndrome. The relevance of the GLP-2 system for cardiovascular disease is unknown. Purpose The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… 20 , 21 Circulating level of GLP-2 was recently found to be increased in patients with AMI. 22 Therefore, we determined to investigate whether GLP-2 could protect the gut barrier, restore intestinal microbiota dysbiosis, and thus alleviate gut microbial translocation under myocardial I/R injury. We first induced myocardial I/R injury in mice, 600 μg/kg degradation-resistant GLP-2 analogue dissolved in saline was injected subcutaneously immediately after reperfusion and continuously delivered twice daily for 3 days.…”
Section: Resultsmentioning
confidence: 99%
“… 20 , 21 Circulating level of GLP-2 was recently found to be increased in patients with AMI. 22 Therefore, we determined to investigate whether GLP-2 could protect the gut barrier, restore intestinal microbiota dysbiosis, and thus alleviate gut microbial translocation under myocardial I/R injury. We first induced myocardial I/R injury in mice, 600 μg/kg degradation-resistant GLP-2 analogue dissolved in saline was injected subcutaneously immediately after reperfusion and continuously delivered twice daily for 3 days.…”
Section: Resultsmentioning
confidence: 99%
“…The same cell population produces GLP-1 in response to nutritional but also inflammatory stimuli, leading to elevated GLP-1 levels in patients with acute myocardial infarction or sepsis [4,31]. Importantly, GLP-1 was found to be an excellent and independent predictor for future cardiovascular events or mortality in both groups of patients, demonstrating a relevant interaction between the cardiovascular system and the gut [5,32]. Similar predictive power was not detected for PYY as an additional gut-derived peptide in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have identified gastrointestinal hormones as modulators of cardiovascular risk. The gut-derived peptide GLP-1 was found to be secreted in response to acute myocardial infarction and to independently predict adverse outcome in this patient population [4,5]. Importantly, GLP-1 receptor agonists reduced cardiovascular events in high-risk patients with diabetes [6][7][8][9].…”
Section: Introductionmentioning
confidence: 95%
“…Recently, the research by Kahles et al [ 98 ] demonstrated that GLP-1 is a powerful biomarker of CV events and death in patients with MI. In this study, 918 patients hospitalized for MI (321 with STEMI and 597 with NSTEMI; mean age (SD) = 66.9 (12.7) years; 73.2% male) were observed for CV outcomes in long-term follow up.…”
Section: Current Knowledge In Atherosclerosis and Coronary Artery Dis...mentioning
confidence: 99%